Standard-dose gentamicin does not increase risk of patent ductus arteriosus - Ayana Kishibuchi; Toru Akaike; Susumu Minamisawa (Elsevier, 2020)
Background: Rates of patent ductus arteriosus (PDA) and infection are high in preterm infants. Preterm infants with infection are more likely to develop symptomatic PDA, a potentially fatal disease. Clinically, gentamicin is widely used for early-onset infection in neonates including preterm infants. A recent study demonstrated that standard-dose gentamicin itself, not infection, increased risk of PDA in mice, suggesting that gentamicin should be avoided in neonates with a risk of PDA. This claim has been insufficiently investigated in subsequent in-vivo experiments. We reevaluated the in-vivo effect of standard-dose gentamicin on patency of the rat ductus arteriosus (DA). Methods: 1) To evaluate the effect of gentamicin on DA patency duration, gentamicin was intraperitoneally injected immediately after birth. 2) To evaluate the effect of gentamicin on DA reopening, gentamicin was intraperitoneally injected 30 min after birth. In both scenarios, 30 min after gentamicin administration, rapid whole-body freezing was performed and the inner diameter of the DA was measured. Results: Standard-dose gentamicin (5 μg/g) did not prolong patency of the DA or increase the likelihood of DA reopening in rat neonates. High-dose gentamicin (100 μg/g), however, significantly prolonged patency of the DA and was associated with DA reopening in rat neonates, although the dilative effect did not reach statistical significance. Conclusion: Standard-dose gentamicin does not increase the risk of PDA in rat neonates. This study suggests that standard-dose gentamicin can be used to treat infection in neonates without increasing PDA morbidity. Key Words: ductus arteriosus, gentamicin, infection, patent ductus arteriosus, preterm infants